Transrectal ultrasonographic diagnosis of jejunoileal intussusception in a cow - Karapinar, Tolga; Kom, Mustafa (I F P Media, 2007)
[Abstract Not Available]
Keywords: Bovine Intestinal Surgery; Ileocecal Intussusception; Cattle; Horses